Effects of annealing on texture evolution of cross shear rolled high-purity Al foils. Issue 1 (April 2015) - Wang, L; Liu, Y; Song, X; He, J; Zuo, L
Abstract: The effects of annealing on recrystallization texture of cross shear rolled high-purity Al foil were investigated by orientation distribution functions (ODFs) and electron backscattered diffraction (EBSD). The results show that the intermediate annealing is beneficial to the development of the cube texture. The cube texture can be promoted by annealing, and the critical annealing temperature is about 280 °C. The cubic orientation grains firstly nucleate, and then expand into other grains with a high growth speed, and large angle grain boundary ratio increases, finally can swallow up most of the original grains, which results in the cube texture